Making periodontal risk visible: the role of artificial intelligence in recall adherence - Prajakta Karkare (Frontiers in Dental Medicine, 2026)
Supportive periodontal care is essential for maintaining periodontal stability after active therapy, yet adherence to periodontal maintenance remains difficult. Once bleeding, halitosis or other presenting concerns improve, some patients may interpret the disease as resolved and the maintenance visit as “just a clean.” This Perspective uses the intention–behaviour gap to examine behavioural, financial and health-literacy barriers to continued supportive care. It then considers a narrower, testable hypothesis: artificial intelligence (AI) might assist clinicians in organising clinician-verified periodontal information and presenting it through personalised visual summaries or prompts. Evidence that AI improves periodontal recall attendance is currently sparse; most dental AI research concerns image interpretation or classification, and the only directly relevant periodontal adherence study is proof-of-concept. Proposed risk projections are therefore presented as a distant research concept rather than a clinically validated tool. AI should not replace clinical judgement, and any future system would require validation, transparent uncertainty, consent, governance, equity safeguards and comparison with simpler non-AI interventions.